Microbial Communities in Sediments From Four Mildly Acidic Ephemeral Salt Lakes in the Yilgarn Craton (Australia) – Terrestrial Analogs to Ancient Mars - Aerts, Joost W.; van Spanning, Rob J. M.; Flahaut, Jessica; Molenaar, Douwe; Bland, Phil A.; Genge, Matt J.; Ehrenfreund, Pascale; Martins, Zita (Frontiers in Microbiology, 2019)
The Yilgarn Craton in Australia has a large number of naturally occurring shallow ephemeral lakes underlain by a dendritic system of paleodrainage channels. Processes like evaporation, flooding, erosion, as well as inflow of saline, often acidic and ion-rich groundwater contribute to the (dynamic) nature of the lakes and the composition of the sediments. The region has previously been described as an analogue environment for early Mars due to its geological and geophysical similarities. Here, we investigated sediment samples of four lake environments aimed at getting a fundamental understanding of the native microbial communities and the mineralogical and (bio)chemical composition of the sediments they are associated with. The dominant mineral phases in the sediments were quartz, feldspars and amphiboles, while halite and gypsum were the only evaporites detected. Element analysis revealed a rich and complex image, in which silicon, iron and aluminum were the dominant ions, but relative high concentrations of trace elements such as strontium, chromium, zirconium and barium were also found. The concentrations of organic carbon, nitrogen and phosphorus were generally low. 16S amplicon sequencing on the Illumina platform showed the presence of diverse microbial communities in all four lake environments. We found that most of the communities were dominated by extremely halophilic Archaea of the Halobacteriaceae family. The dynamic nature of these lakes appears to influence the biological, biochemical and geological components of the ecosystem to a large effect. Inter- and intra-lake variations in the distributions of microbial communities were significant, and could only to a minor degree be explained by underlying environmental conditions. The communities are likely significantly influenced by small scale local effects caused by variations in geological settings and dynamic interactions caused by aeolian transport and flooding and evaporation events.